DIAGNOSTIC ACCURACY OF CHEST X-RAY IN TRACHEOBRONCHIAL FOREIGN BODY ASPIRATION IN PAEDIATRIC PATIENTS - Sattar, Abdul; Ahmad, Ijaz; Javed, Azhar Mehmood; Anjum, Sadia (Journal of Ayub Medical College Abbottabad, 2011)
Objective: To evaluate the diagnostic value of chest X-Ray in tracheobronchial foreign body aspiration among group of children in southern Punjab. Methods: The Cross sectional/comparative diagnostic procedural study was conducted in the Department of Radiology, Nishtar Medical College and Children Hospital Complex, Multan from January 2009-January 2011. Chest CT was performed in 45 consecutive children with suspected foreign body aspiration, and plain chest X-ray was evaluated at the same time. Multi-planar reformatted imaging with virtual bronchoscopy was carried out after Multidetector CT examination. Findings on plain X-Ray and CT scan chest were noted in each patient. Results: All 42 (100%) patients with tracheobronchial foreign bodies were identified by chest CT. Three patients avoided unnecessary operations due to negative CT scan for foreign body with alternate diagnosis. Right main stem bronchus was the most common location of foreign body 20 (47.6%) and air trapping was the most common associated finding (28.5%). Sixteen of the 45 (35.5%) patients had no abnormalities on plain X-Ray. The difference between Multi-detector CT and plain X-Ray results was statistically significant (p<0.001). The sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and accuracy of chest X-Ray in this study were 66.6%, 50%, 89.6%, 18.7% and 64.4% respectively. Conclusion: Chest X-Ray is not specific for diagnosis of foreign body aspiration and a normal chest X-Ray does not always rule out the diagnosis of foreign body aspiration in patients with a history suggestive of foreign body aspiration and positive physical examination. Keywords: Foreign body aspiration, Chest X-Ray, Multi-detector CT scan